Do internship students do well in a clinical environment? A qualitative naturistic study - Fadiyah Jadid Alanazi; Mada Huwaydi M Alenezi; Atheer Abdullah N Alanazi; Taif Salem R Alanazi (Belitung Raya Foundation, Indonesia, 2023)
Background: The internship year marks the culmination of the nursing program across all Saudi universities, bridging theoretical learning and practical application. The significance of the internship year lies in the application of skills acquired during the preceding years of study. Understanding interns’ experiences, identifying influences, and sharing their recommendations for best practices become crucial. Objective: This study aimed to explore the experiences of internship students and address the challenges they encountered in a clinical environment. Methods: A qualitative naturistic descriptive approach was employed, involving 20 purposively selected participants from internship students in two regions in Saudi Arabia. Data were collected in January 2023 through semi-structured interviews, focus group discussions, and observation. A conventional content analysis approach was used for data analysis. Results: Four major themes were generated: 1) Transferring Shock, 2) Self-Learning, 3) Supportive Environments, and 4) Factors Facilitating Learning. Transferring Shock comprised two subthemes: feeling lost and feeling left out. Conclusion: Internship students acknowledged the utility of orientation and mentorship programs in advancing the practical skills of new nurses and enhancing patient safety. The findings also indicated that those with prior preparation and robust communication skills reported a positive experience. Consequently, integrating communication courses into the nursing education curriculum could be beneficial. Establishing a supportive learning environment for nursing interns is imperative to address challenges and ensure the delivery of safe and effective patient care.